Diagnostic cervical excision in patients with HPV positivity, cytological abnormalities- and preoperative cervical stenosis - Agnieszka Denecke; Duaa Emar; Peter Hillemanns; Dhanya Ramachandran; Bianca Brüning; Matthias Jentschke (BMC, 2024)
Abstract Aim There is currently no protocol for classifying patients with HPV persistence and preoperative stenosis of the cervical canal. This has a significant impact on cytology results, colposcopy results and the possibility of obtaining reliable cervical histology outcomes. Our analysis clearly shows that colposcopy and cytology underestimate the histological results in patients with limited visibility due to the presence of a type 3 transformation zone (TZ). Our analysis revealed a significant discrepancy between the colposcopy and cytology results and the histological outcomes. Insufficient colposcopy led to the underdiagnosis of dysplastic lesions in patients with a type 3 TZ and cervical stenosis. In the case of repeated cytological abnormalities and inadequate colposcopy examination, it is crucial to perform a diagnostic conization to exclude high-grade dysplastic changes and cervical carcinoma. Methods We conducted a retrospective analysis of 1,021 conizations performed in tertiary care hospital in Wolfsburg, Germany between 2014 and 2020. Of these surgical procedures, 89 were diagnostic conizations. In our analysis, we defined diagnostic conization as a procedure performed when there is HPV persistence and repeated cytologic abnormalities in combination with a type 3 TZ, and when it is not possible to retrieve a relevant cervical histology sample. Results In this period, 8.7% of all conizations were diagnostic excisions. We found histological abnormalities in 48 of 89 patients (53.9%). The histological examination of the excised cone revealed high-grade cervical intraepithelial neoplasia (CIN/HSIL) in 9 patients (10.1%) and CIN 2+ (HSIL) in 23 out of the 89 patients (25.8%). Two cases of early-stage cervical carcinoma (FIGO IA1 and FIGO IA2) were confirmed (2.3%). Conclusion Patients with cervical stenosis, high-risk HPV persistence and repeated cytological abnormalities are at high risk of undetected high-grade cervical dysplasia. Histologic confirmation must be ensured in this patient consultation and this can be achieved by performing diagnostic excisions.